Red Emission Of Thin Film Electroluminescent Device Based On p-GaN. - L, S Chuah; Hassan, Z; Abu Hassan, H (2007)

(untitled)
High quality GaN layers doped with Mg were grown on Si(111) substrates using high temperature AlN as buffer layer by using radio-frequency molecular beam epitaxy (RF-MBE).